1984
DOI: 10.1002/anie.198409631
|View full text |Cite
|
Sign up to set email alerts
|

Second Order Jahn‐Teller Effect in Hexahalogenotellurates(IV): Statically Distorted Anion in Ca(H2O,HF)7TeBr6

Abstract: The gene fragments were ligated with the aid of polynucleotide ligase to form the complete gene (Fig. 2), which was then inserted into a plasmid opened with EcoRI and IFN-I IFN-I1 IFN-111 t p I F N Eco R I Barn H I Fig. 2. Cloning vectors pUC8 and pUC9 with the gene fragments IFN-I-IFN-Ill and expression vectors pMX2 with the tac-regulation unit. For the construction of the expression vector pMX2 the gene fragments IFN-I-IFN-111 were first subcloned in pUC8 and pUC9, respectively, as follows: 1 pg of the pUC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Abriel (75)(76)(77)(78)(79) found that in contrast to the appreciably distorted TeC16 octahedron in [H3N(CH2)3NH3]-TeC16 the SnC16 octahedron in the corresponding hexachlorostannate(1V) is undistorted. The distortion observed in the TeC162-and ~e~r 6 ' -ions is accompanied by lifting of the degeneracy of the v3(tlu) and v4(tlu) fundamentals in the ir spectra; however, the v3 and v4 absorption bands appear to be broadened even in cubic Rb2TeBr6, where Te is at a site of Oh symmetry.…”
Section: Stereochemically Inactive Lp In Crystalsmentioning
confidence: 99%
“…Abriel (75)(76)(77)(78)(79) found that in contrast to the appreciably distorted TeC16 octahedron in [H3N(CH2)3NH3]-TeC16 the SnC16 octahedron in the corresponding hexachlorostannate(1V) is undistorted. The distortion observed in the TeC162-and ~e~r 6 ' -ions is accompanied by lifting of the degeneracy of the v3(tlu) and v4(tlu) fundamentals in the ir spectra; however, the v3 and v4 absorption bands appear to be broadened even in cubic Rb2TeBr6, where Te is at a site of Oh symmetry.…”
Section: Stereochemically Inactive Lp In Crystalsmentioning
confidence: 99%
“…The slightly larger Se atom in SeF 6 2- is the borderline case. If the central atom sizes are kept equal, but the size of the ligand atom is increased as in TeCl 6 2- , TeBr 6 2- , and TeI 6 2- , then again the structure changes toward octahedral. , The resulting prediction is also fulfilled, namely that with the increasing number of ligands, the sterical activity of the nonbonding electron pair diminishes and disappears. XeF 5 + has a square pyramidal umbrella structure, with the sterically active lone pair occupying an apical site.…”
Section: The Problem Of the Sterically Active Or Nonactive Electron P...mentioning
confidence: 94%
“…In such highly symmetric molecules, this is difficult to prove experimentally. But derivatives of the kind F 5 Mo-OR and F 5 W-OR (with R ) CH 2 -CF 3 and C 6 F 5 ) show coalescence of the chemically different fluorine atoms in the 19 F NMR spectrum not much above room temperature. 46 Chemical thinking immediately brings up mixed substituted compounds (CH 3 ) x MoX 6-x and (CH 3 ) x WX 6-x (with X ) F, Cl, OR) to answer the question, at what stage of substitution the change occurs from trigonal prism to octahedron or vice versa.…”
Section: Transition Metal Complexesmentioning
confidence: 98%
“…These materials include halide-perovskite-derived complexes, the most promising of which are complexes with the general formula A 2 BX 6 (where A is organic or inorganic cations, B are so-called s 2 -ions (Ti IV , Hf IV , Zr IV , Pd IV , Pb II , Sn IV , Te IV , Sb III , and Bi III ), and X are halogens (F, Cl, Br, and I)). These compounds possess interesting luminescent, optical, dielectric, and magnetic properties and have applications in modern semiconductor devices. Currently, these materials are used to increase the power of photovoltaic modules or increase the luminescence quantum yield. …”
Section: Introductionmentioning
confidence: 99%
“…On binding cations, they form structures with densely packed layers. Crystals with [TeCl 6 ] 2– and [TeBr 6 ] 2– anions have strong luminescent properties, ,,, whereas those with [TeI 6 ] 2– anions show polymorphism and phase transitions. An interesting feature of these crystals is that the probability of transitions to the excited states depends mainly on the local environment of the s 2 -ion, i.e. the halogen atom.…”
Section: Introductionmentioning
confidence: 99%